The Commercialization of the Microfinance Industry: Is There a "Personal Mission Drift" Among Credit Officers? - Leif Atle Beisland; Bert D'Espallier; Roy Mersland (Journal of Business Ethics, 2019)
Recent research suggests that many microfinance institutions increasingly focus on financial performance at the expense of the social component of their dual objectives. Existing studies typically assume that capital providers and managers mainly drive this so-called mission drift. In this study, we investigate whether `personal mission drift' at the credit officer level can further explain the reduced emphasis on poorer clients among microfinance institutions. We present both qualitative and quantitative evidence that more experienced credit officers tend to serve fewer vulnerable clients. Specifically, we show that all else being equal, credit officer experience is negatively correlated with the provision of small loans, loans to young clients, and loans to clients with disabilities. Our qualitative analysis suggests that perceived client risk and preferences for increased time efficiency mainly drive more experienced credit officers' relative neglect of more vulnerable clients. This drift appears to be reinforced by the industry's incentive schemes. Therefore, credit officer incentives and training should be designed to prevent this mission drift, which is observed at the microfinance institution level but is actually initiated at the credit officer level.
Keywords: 650